Advancements in the Treatment of Necrotizing Otitis Externa with Hyperbaric Oxygen: A Systematic Review - Bazzal, Hassan Al; Hassan, Firas; Tlais, Mohamad; Tlaiss, Yehya (International Archives of Otorhinolaryngology, 2025)
Necrotizing otitis externa (NOE), also known as malignant otitis externa (MOE), is a severe infection that begins in the external auditory canal and can extend to adjacent tissues and bone. It primarily affects elderly, diabetic, and immuno-compromised patients. Despite the advancements in antibiotics and surgical interventions, NOE remains a condition with significant morbidity and mortality.To evaluate the efficacy of hyperbaric oxygen therapy (HBOT) as an adjunctive treatment for NOE, focusing on clinical outcomes and the potential benefits in refractory or advanced cases.We conducted a comprehensive literature search on the PubMed/MEDLINE and Cochrane Library databases for articles published from January 1980 to December 2023. The search terms included hyperbaric oxygen therapy, necrotizing otitis externa, and refractory otitis. A total of 8 studies met the inclusion criteria, comprising case reports, observational studies, and case series. Study quality was assessed through the Cochrane Risk of Bias tool and the Newcastle-Ottawa Scale.The results indicate that HBOT shows promise in the treatment of NOE, with several studies reporting complete resolution of infection and prevention of recurrence, especially in refractory cases.The current evidence is insufficient to establish HBOT as a standard treatment for NOE; however, its potential benefits in improving clinical outcomes and reducing morbidity are significant. High-quality research, including randomized controlled trials, is necessary to validate the role of HBOT in NOE treatment. Where hyperbaric facilities are accessible, HBOT should be considered for refractory NOE cases.
Keywords: hyperbaric oxygenation; otitis externa; necrotizing diabetes mellitus; adjuvant therapy